Diabetes distress: understanding the hidden struggles of living with diabetes and exploring intervention strategies. Issue 1075 (31st March 2015) - Berry, Emma; Lockhart, Sam; Davies, Mark; Lindsay, John R; Dempster, Martin
ABSTRACT: Diabetes distress is a rational emotional response to the threat of a life-changing illness. Distinct from depression, it is conceptually rooted in the demands of diabetes management and is a product of emotional adjustment. Diabetes distress has been found to be significantly associated with glycated haemoglobin (HbA1c ) level and the likelihood of an individual adopting self-care behaviours. The lack of perceived support from family, friends and healthcare professionals significantly contributes to elevated diabetes distress, and this issue tends to be overlooked when designing interventions. Pioneering large-scale research, DAWN2, gives voices to the families of those with diabetes and reaffirms the need to consider psychosocial factors in routine diabetes care. Structured diabetes education programmes are the most widely used in helping individuals cope with diabetes, but they tend not to include the psychological or interpersonal aspects of diabetes management in their curricula. The need for health practitioners, irrespective of background, to demonstrate an understanding of diabetes distress and to actively engage in discussion with individuals struggling to cope with diabetes is emphasised.